Promoting integrated Caribbean capital markets - role of credit ratings - Raman, S. Venkat ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2005)
Focuses on aspects of the information and disclosure practices, the current status compared to international best practices and some recommendations to overcome the current problems.